Assess the Level of Stress and Coping Strategies among Senior Citizens (International Journal of Scientific Research in Science and Technology, 2025)
BACKGROUND Aging is a natural process accompanied by various physical, emotional, and social changes that can significantly affect the mental well-being of the elderly. Stress among senior citizens is a growing concern, particularly in rural areas where access to mental health services and awareness about coping mechanisms is limited. Coping strategies play a crucial role in managing stress and maintaining psychological health in old age. INTRODUCTIONElderly individuals often face challenges such as loneliness, financial insecurity, health issues, and lack of social support, which can lead to increased stress. Effective coping strategies are essential for managing stress and maintaining a good quality of life in old age. However, many senior citizens remain unaware of healthy coping techniques due to limited access to health education and support systems. This study aims to assess the level of stress and coping strategies among senior citizens in a selected rural community area and to provide an information booklet to enhance their awareness and ability to manage stress effectively. AIM/OBJECTIVESTo assess the level of stress and coping strategies among senior citizens in a selected rural community area of Village Sunder Nagar, District Mandi (Himachal Pradesh), with a view to provide an information booklet.   METHODOLOGYThe study adopted a quantitative descriptive research approach to assess the level of stress and coping strategies among senior citizens in a selected rural community area. A total of 60 senior citizens were enrolled on the study by using a purposive sampling technique. A 5-point Likert-type rating scale was used to assess the level of stress and coping strategies among senior citizens. RESULTThe study was conducted among 60 senior citizens residing in a selected rural community area of Village Sunder Nagar, District Mandi (Himachal Pradesh), to assess their level of stress and coping strategies. When assessed for stress levels using a structured 10-item rating scale, the findings showed that 56.7% of the participants experienced moderate stress, while 26.6% reported high levels of stress. Only 16.7% of the participants had low stress levels. The mean stress score was 31.4 ± 7.6, indicating that stress was prevalent to a moderate extent among the elderly in this rural setting.Coping strategies were also assessed using a 10-item rating scale. The results indicated that 63.3% of the participants had moderate coping strategies, 23.4% demonstrated good coping, while 13.3% had poor coping mechanisms. The mean coping score was 33.6 ± 6.8, suggesting that while most senior citizens were using some form of coping techniques, there was still room for improvement, especially among those with poor coping ability.Further analysis using the chi-square test revealed a significant association between stress levels and certain demographic variables, specifically age (p = 0.045) and marital status (p = 0.047). However, no significant association was found between stress levels and variables like gender or educational status. CONCLUSIONThe findings revealed that a majority of the senior citizens experienced moderate levels of stress, and while many employed moderate coping strategies, a notable percentage had either high stress or poor coping abilities.
Keywords: Stress; Coping Strategies; Senior Citizens; Information Booklet